Language and infant mortality in a large canadian province - Auger, Nathalie; Bilodeau-Bertrand, M.; Costopoulos, A. (Public Health, 2016)
Objectives Infant mortality in minority populations of Canada is poorly understood, despite evidence of ethnic inequality in other countries. We studied infant mortality in different linguistic groups of Quebec, and assessed how language and deprivation impacted rates over time. Study design Population-level study of vital statistics data for 1,985,287 live births and 10,283 infant deaths reported in Quebec from 1989 through 2012. Methods We computed infant mortality rates for French, English, and foreign languages according to level of material deprivation. Using Kitagawa's method, we evaluated the impact of changes in mortality rates, and population distribution of language groups, on infant mortality in the province. Results Infant mortality declined from 6.05 to 4.61 per 1000 between 1989–1994 and 2007–2012. Most of the decline was driven by Francophones who contributed 1.39 fewer deaths per 1000 births over time, and Anglophones of wealthy and middle socio-economic status who contributed 0.13 fewer deaths per 1000 births. The foreign language population and poor Anglophones contributed more births over time, including 0.08 and 0.02 more deaths per 1000 births, respectively. Mortality decreased for Francophones and Anglophones in each level of deprivation. Rates were lower for foreign languages, but increased over time, especially for the poor. Conclusions Infant mortality rates decreased for Francophones and Anglophones in Quebec, but increased for foreign languages. Poor Anglophones and individuals of foreign languages contributed more births over time, and slowed the decrease in infant mortality. Language may be useful for identifying inequality in infant mortality in multicultural nations.

Inequality in fetal autopsy in Canada - Auger, Nathalie; Tiandrazana, Rémi- Claude; Healy-Profitós, Jessica; Costopoulos, André (Journal of health care for the poor and underserved, 2016)
Purpose. Inequality in use of fetal autopsy is poorly understood, despite the importance of autopsy in establishing the cause of stillbirth for future prevention. We examined fetal autopsy rates between linguistic minorities in Quebec, Canada, and assessed trends over three decades. Methods. Using registry data on 11,992 stillbirths from 1981–2011, we calculated fetal autopsy rates for Francophones, Anglophones, and Allophones by decade. Results. We found lower fetal autopsy rates for Allophones (54.4%) than Francophones (68.5%) and Anglophones (63.4%), but rates decreased over time for all language groups. After 2000, Allophones had 25% higher risk of non-autopsy relative to Francophones, with 8.8 fewer autopsies for every 100 stillbirths. Allophones who were not autopsied had 32% higher risk of having an undetermined cause of death. Conclusion. Inequality in use of fetal autopsy may be widespread for minorities in Canada. Efforts to decrease stillbirth in minorities may require policies to increase autopsy rates.

Impact des barrières linguistiques sur la sécurité des patients et la qualité des soins. Rapport final - Bowen, Sarah (Société Santé en français, 2015)

The impact of language barriers on patient safety and quality of care. Final report - Bowen, Sarah (Société Santé en français, 2015)

Multilingualism (but not always bilingualism) delays the onset of Alzheimer disease: Evidence from a bilingual community - Chertkow, Howard; Whitehead, Victor; Phillips, Natalie; Wolfson, Christina; Atherton, Julie; Bergman, Howard (Alzheimer Disease and Associated Disorders, 2010)
A recent paper by Bialystok et al in Neuropsychologia (vol. 45, pgs. 459 to 464) suggested that early bilingualism produced a statistically significant 4.1-year delay in onset of memory loss symptoms in older individuals with Alzheimer disease, possibly reflecting an increase in the cognitive reserve of these individuals. That study focused on multilingual elderly patients of whom 90% were immigrants. Our memory clinic, in Montreal Canada, has the advantage of having a large set of individuals who are either multilingual immigrants to Canada, or who are nonimmigrants but raised in both official languages of Canada—French and English. We thus attempted to replicate the above findings using a larger cohort in a different setting. We examined age at diagnosis of Alzheimer disease and age at symptom onset for all unilingual versus multilingual participants, and then for those who were nonimmigrant English/French bilinguals. Overall, we found a small but significant protective effect of more than 2 languages spoken, but we found no significant benefit in bilinguals overall in relation to age at diagnosis or age at symptom onset. However, in the immigrant group, the results mirrored those of Bialystok et al with 2 or more languages delaying the diagnosis of Alzheimer disease by almost 5 years. A trend toward the same effect was also seen in nonimmigrants whose first language was French. In contrast, in nonimmigrants whose first language was English, no such effect was found. These results are discussed in relation to the earlier findings and the theory of cognitive reserve.

Le potentiel d'offre et de demande de Services médicaux et diagnostiques dans la langue de communautés minoritaires : où se situe le français en Colombie-Britannique? - Giguère, Louis; Conway, Brian (Reflets, 2014)
Une étude comparative du potentiel de services médicaux dans les langues minoritaires de Colombie-Britannique révèle que des médecins non-francophones parlant français génèrent une retombée linguistique qui amplifie l’offre potentielle de services de santé et de services sociaux en français de façon dramatique. Ce mécanisme structurant s’appliquerait aux autres professions de la santé et des services sociaux, partout au Canada et il serait plus prononcé plus le contexte est minoritaire. Les communautés francophones doivent faire plus pour identifier, engager et outiller les professionnels et professionnelles « francophiles » et elles doivent élaborer une logique d’équité innovatrice pour dégager le potentiel d’offre de services de santé et de services sociaux en français dans un contexte multilingue. Mots-clés : CFASM, CLOSM, médecins parlant français, minorités linguistiques, équité, services d’interprétation, offre et demande

Sources de données de Statistique Canada sur les minorités de langue officielle (n°91-549 -X) - Lafrenière, Sylvie (Statistique Canada, 2013)

Statistics Canada data sources on official-language minorities (n°91-549-X-n°2) - Lafrenière, Sylvie (Statistics Canada, 2013)

English, French and official language minorities in Canada: Census of population, 2016 (n°98-200-X2016011) - Lepage, Jean-François (Statistics Canada, 2017)
fs-ref-orig: Lepage, J.-F. (2017). English, French and official language minorities in Canada: Census of population, 2016 (n°98-200-X2016011). Statistics Canada. fs-code-orig: Lepage-2017b

Le français, l’anglais et les minorités de langue officielle au Canada : recensement de la population, 2016 (n°98-200-X2016011) - Lepage, Jean-François (Statistique Canada, 2017)
fs-ref-orig: Lepage, J.-F. (2017). Le français, l’anglais et les minorités de langue officielle au Canada : recensement de la population, 2016 (n°98-200-X2016011). Statistique Canada. fs-code-orig: Lepage-2017a

Linguistic mortality gradients in Quebec and the role of migrant composition - Lo, Ernest; Tu, Mai Thanh; Trempe, Normand; Auger, Nathalie (Canadian Journal of Public Health, 2018)
Objective Anglophones and Allophones in Quebec (Canada) have lower mortality than Francophones, despite being linguistic minorities. This study assesses whether (1) language is a risk factor for mortality after accounting for migrant composition and (2) interprovincial migrants differ in mortality with respect to Quebec-born individuals. Methods We analyzed death records between 2004 and 2008 from Quebec (all-cause and main causes) and population data from the 2006 census to estimate age-adjusted mortality rates according to language and migrant status. Risk ratios by language and migrant status, adjusted for age, sex, and socioeconomic status, were estimated using Poisson generalized estimating equations. Results Francophone Quebec-borns had the highest mortality. Among Quebec-borns, Anglophones [RR= 0.85, 95% CI (0.79–0.91)] and Allophones [RR = 0.16, 95 %CI (0.12–0.22)] had lower mortality relative to Francophones. Interprovincial migrants had lower mortality (Anglophones [RR = 0.58, 95% CI (0.53–0.63)], Francophones [RR = 0.55, 95% CI (0.50–0.60)]) relative to Francophone Quebec-borns (Allophones were excluded due to small sample size). Among immigrants, mortality was lower for Francophones [RR = 0.62, 95% CI (0.57–0.67] and Allophones [RR = 0.35, 95% CI (0.31–0.38], but not Anglophones [RR = 0.92, 95% CI (0.84–1.01)], relative to Francophone Quebec-borns. Conclusion In Quebec, linguistic disparities in mortality remained after accounting for migrant status, and both Francophone and Anglophone interprovincial migrants in Quebec had lower mortality than Quebec-born Francophones. Public health initiatives to reduce linguistic disparities in health should account for migrant status.

À l’intersection des définitions de langues : portrait des communautés linguistiques au Québec et dans les réseaux territoriaux de services en 2016. La langue, déterminant de l'état de santé et de la qualité des services - Lussier, Marie-Hélène; Tu, Mai Thanh; Blaser, Christine (Institut national de santé publique du Québec, 2019)

At the intersection of language definitions: A portrait of linguistic communities in Québec and its territorial service networks in 2016. Language as determinant of health and quality of services - Lussier, Marie-Hélène; Tu, Mai Thanh; Blaser, Christine (Institut national de santé publique du Québec, 2019)

Workforce utilization of visible and linguistic minorities in Canadian nursing - Premji, Stephanie; Etowa, Josephine. B. (Journal of Nursing Management, 2012)
Background There is ample evidence of ethnic and linguistic segregation in the Canadian labour market. However, it is unknown if there is equitable representation of visible and linguistic minorities in nursing professions. Methods We cross-tabulated aggregate data from Statistics Canada’s 2006 Census. Analyses examined the distribution of visible and linguistic minorities, including visible minority sub-groups, among health managers, head nurses, registered nurses, licensed nurses and nurse aides for Canada and major cities as well as by gender. Results In Canada and its major cities, a pyramidal structure was found whereby visible and linguistic minorities, women in particular, were under-represented in managerial positions and over-represented in lower ranking positions. Blacks and Filipinos were generally well represented across nursing professions; however, other visible minority sub-groups lacked representation. Conclusions Diversity initiatives at all levels can play a role in promoting better access to and quality of care for minority populations through the increased cultural and linguistic competence of care providers and organizations.

Recommandation du Réseau. Application pratique de la Définition inclusive de francophone (DIF) - Réseau des services de santé en français de l’Est de l’Ontario (Application pratique de la Définition inclusive de francophone (DIF), 2013)

Réseau recommendation. Application of the Inclusive definition of Francophone (IDF) - Réseau des services de santé en français de l’Est de l’Ontario (Application of the Inclusive definition of Francophone (IDF), 2013)

Potential for patient-physician language discordance in Ontario - Sears, Jennifer; Khan, Kamran; Ardern, Chris . I.; Tamim, Hala (BMC Health Services Research, 2013)
Background Patient-Physician language discordance occurs when the patient and physician lack proficiency in the same language(s). Previous literature suggests language discordant clinical encounters compromise patient quality of care and health outcomes. The objective of this study was to quantify and visualize the linguistic and spatial mismatch between Ontario’s population not proficient in English or French but proficient in one of the top five non-official languages and the physicians who are proficient in the same non-official language. Methods Using data from the 2006 Canadian census and the 2006 Canadian Medical Directory, we determined the number of non-English/non-French (NENF) speaking individuals and the number of Ontario physicians proficient in the top five non-official languages in each census division (CD) of Ontario. For each non-official language, we produced bi-variate choropleth maps of Ontario, broken down into the 49 CDs, to determine which CDs had the highest risk of language discordant clinical encounters. Results According to the 2006 Canadian census, the top five non-official languages spoken by Ontario’s NENF population were: Chinese, Italian, Punjabi, Portuguese and Spanish. For each of the top five non-official languages, there were at least 5 census divisions with a NENF population speaking a non-official language without any primary care physicians proficient in that non-official language. The size of NENF populations within these CDs ranged from 10 individuals to 1,470 individuals. Conclusions Understanding the linguistic capabilities of Ontario’s immigrant population & the linguistic capabilities of Ontario’s primary care physicians is essential to ensure equal access and quality of healthcare. As immigration continues to increase, we may find that the linguistic needs of Ontario’s immigrant population diverge from the linguistic capabilities of Ontario’s primary care physicians. Further research on the language discordance in Ontario is needed in order to reduce the risk of language discordant clinical encounters and the negative health outcomes associated with these encounters.

Assessment of validity for the “language spoken at home” variable in Québec death records: Summary. Language, determinant of health status and of services' quality - Trempe, Normand; Boivin, Marie-Claude; Lo, Ernest; Diogo Barry, Amado (Institut national de santé publique du Québec, 2012)

La validité de la variable « Langue d’usage à la maison » du Fichier des décès du Québec : synthèse. La langue, déterminant de l'état de santé et de la qualité des services - Trempe, Normand; Boivin, marie-claude; Lo, Ernest; Diogo Barry, Amado (Institut national de santé publique du Québec, 2012)

Portrait de la prématurité et des naissances ayant un faible poids pour l’âge gestationnel dans les communautés linguistiques au Québec, 1989 à 2010 - Tu, Mai Thanh; Bilodeau-Bertrand, M.; Auger, Marianne (Institut national de santé publique du Québec, 2018)
fs-ref-orig: Tu, M. T., Bilodeau-Bertrand, M. et Auger, N. (2018). Portrait de la prématurité et des naissances ayant un faible poids pour l’âge gestationnel dans les communautés linguistiques au Québec, 1989 à 2010. Institut national de santé publique du Québec. fs-code-orig: Tu-2018c

Portrait of preterm and small-for-gestational-age births by linguistic community in Québec, 1989 to 2010 - Tu, Mai Thanh; Bilodeau-Bertrand, Marianne; Auger, Nathalie (Institut national de santé publique du Québec, 2018)
fs-ref-orig: Tu, M. T., Bilodeau-Bertrand, M., & Auger, N. (2018). Portrait of preterm and small-for-gestational-age births by linguistic community in Québec, 1989 to 2010. Institut national de santé publique du Québec. fs-code-orig: Tu-2018d

Health profile of linguistic communities in Québec - Tu, Mai. Thanh; Lussier, Marie-Hélène.; Martel, Sylvie; Blaser, Christine (Institut national de santé publique du Québec, 2018)
fs-ref-orig: Tu, M. T., Lussier, M.-H., Martel, S., & Blaser, C. (2018). Health profile of linguistic communities in Québec. Institut national de santé publique du Québec. fs-code-orig: Tu-2018b

Portrait de santé des communautés linguistiques du Québec - Tu, Mai Thanh; Lussier, Marie-Hélène; Martel, Sylvie; Blaser, Christine (Institut national de santé publique du Québec, 2018)
fs-ref-orig: Tu, M. T., Lussier, M.-H., Martel, S. et Blaser, C. (2018). Portrait de santé des communautés linguistiques du Québec. Institut national de santé publique du Québec. fs-code-orig: Tu-2018a

Comparing the rates of mental disorders among different linguistic groups in a representative Canadian population - Vasiliadis, Helen-Maria; Lepnurm, Marje; Tempier, Raymond; Kovess-Masfety, Viviane (Social psychiatry and psychiatric epidemiology, 2012)
Purpose We aimed to determine whether linguistic group influences reported prevalence rates for a number of common mental disorders. Methods Secondary data analyses of the Canadian Community Health Survey cycle 1.2 (CCHS 1.2) were carried out on representative bilingual French and English, monolingual French and English and other language groups in Canada. Past year prevalence of major depression, anxiety disorders (agoraphobia, social phobia, panic disorder) and alcohol abuse/dependence were ascertained using versions of the World Mental Health Composite International Diagnostic Interview (WMH-CIDI) questionnaire. Multivariate data analyses were used to model past year presence of a mental disorder as a function of linguistic group, defined as languages can converse in, and adjusting for socioeconomic, demographic and cultural factors. Results Overall, past year rates for the presence of a common mental disorder were 10.7% (9.7–11.7%) for the bilingual English; 9.0% (8.1–9.9%) for the bilingual French; 10.2% (9.8–10.6) for the monolingual English; 8.5% (7.7–9.3%) for the monolingual French; and 8.3% (6.1–10.4%) for the other language group. After adjusting for a number of socio-demographic, economic and cultural factors, the multivariate analyses showed that the linguistic groups were equally likely to report the presence of a past year common mental disorder. This was also true for comparisons between the bilingual participants responding in French and English. Conclusions The differences observed in the reported crude rates for the presence of mental disorders across the different linguistic groups in Canada were explained by socio-demographic, economic, and factors such as immigration, spoke a third language and province of residence, and not explained by language of interview.